Bibliometric Mapping of Islamic Higher Education Research: Global Perspectives and Emerging - Daud Ridwan; Benny Prasetiya; Febry Suprapto; Khoiriyah Khoiriyah (PT. Caesarindo Triloka Persada, 2026)
This study presents a comprehensive bibliometric mapping and analysis of global research trends in Islamic Higher Education (IHE), drawing upon 1,400 Scopus-indexed publications from 1970 to 2024. Employing advanced bibliometric techniques such as co-authorship, co-citation, and co-word analyses using VOSviewer and Bibliometrix R-package, this research systematically explores publication dynamics, intellectual structures, and emerging thematic directions within the field. The findings reveal a sustained annual growth rate of 10.62%, with a sharp increase since the mid-2000s, indicating a global rise in scholarly interest in IHE as both a religious and socio-academic domain. Southeast Asia particularly Indonesia and Malaysia dominates research output, while international collaboration remains limited. Thematic network visualisations indicate two principal clusters: (1) educational and religious studies, centred on topics such as higher education, Islamic education, and religious moderation; and (2) health and human studies, emphasizing gender, adult learning, and empirical methodologies. The thematic evolution map positions “human,” “female,” and “adult” as motor themes, suggesting growing interdisciplinarity linking Islamic pedagogy with psychology, digital learning, and health education. Conversely, “Islamic higher education” and “Islamic education” appear as emerging or underdeveloped themes, reflecting both conceptual immaturity and potential for future expansion